Studies using concentric ring bifocal and peripheral add multifocal contact lenses to slow myopia progression in school‐aged children: a meta‐analysis. (23rd November 2016) - Li, Shi‐Ming; Kang, Meng‐Tian; Wu, Shan‐Shan; Meng, Bo; Sun, Yun‐Yun; Wei, Shi‐Fei; Liu, Luoru; Peng, Xiaoxia; Chen, Zhuo; Zhang, Fengju; Wang, Ningli
Abstract: Purpose: To evaluate the effect of soft contact lens with concentric ring bifocal and peripheral add multifocal designs on controlling myopia progression in school‐aged children. Methods: We systematically searched MEDLINE, EMBASE, Cochrane Library and reference lists of included trials. Methodological quality of included trials was assessed using Jadad Scale and Newcastle‐Ottawa Quality Assessment Scale items. Results: We identified five randomised controlled trials (RCTs) and three cohort studies with a total of 587 myopic children. Compared with the control group, concentric ring bifocal soft contact lenses showed less myopia progression with a weighted mean difference (WMD) of 0.31 D (95% CI, 0.05~0.57 D, p = 0.02) and less axial elongation with a WMD of −0.12 mm (95% CI, approximately −0.18 to −0.07 mm, p < 0.0001) at 12 months. Relative to the control group, peripheral add multifocal soft contact lenses showed less myopia progression with a WMD of 0.22 D (95% CI 0.14~0.31 D, p < 0.0001) and less axial elongation of −0.10 mm (95% CI −0.13~0.07 mm, p < 0.0001) at 12 months, respectively. The soft contact lenses with concentric ring bifocal and peripheral add multifocal designs produced additional myopia control rates of 30~38% for slowing myopia progression and 31~51% for lessening axial elongation within 24 months. Conclusions: Both concentric ring bifocal and peripheral add multifocal soft contact lenses are clinically effective for controlling myopia in school‐aged children, with an overall myopia control rates of 30~50% over 2 years. Concentric ring bifocal soft contact lenses seem to have greater effect than peripheral add multifocal soft contact lenses.